Efektifitas Upgrading Skill Bahasa Arab di Madrasah Tsanawiyah KHA Wahid Hasyim Bangil - Sofiyulloh; Makhfud Syawaludin; Ahmad Aris Fajarudin; Khoridatul Bahiyyah; Amang Fathurrohman; Ning Mukaromah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Purpose: This study examines the effectiveness of the Arabic language skill upgrading program at Madrasah Tsanawiyah KHA Wahid Hasyim Bangil, focusing on improving students' Arabic proficiency. It aims to explore how structured programs can enhance language skills in Islamic educational settings. Design/methodology/approach: A mixed-method approach was used, combining quantitative data from pre and post-tests with qualitative insights from classroom observations, interviews with teachers and students, and document analysis to evaluate both student performance and teaching practices. Research limitations/implications: The study faced limitations such as time constraints and varying levels of student motivation, which may have influenced results. These factors should be considered for future program improvements. Findings: The findings revealed significant improvements in students' proficiency across all four language skills: reading, writing, listening, and speaking. The program's success is attributed to its structured curriculum, specialized teaching methods, regular assessments, and integration of technology. Originality/value: This research offers valuable insights into effective Arabic language teaching in Islamic educational institutions. It demonstrates how traditional approaches can be enhanced through systematic skill upgrading programs, providing a practical framework for institutions aiming to improve Arabic language education with contemporary teaching methods.